The Structural Complexity In Liszt's Transcription of Beethoven's 'Eroica' Symphony - Wu, Xiangyu; Djahwasi, Herry Rizal; Nasrifan, Mohd Nizam bin (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2025)
This study investigates Franz Liszt’s solo piano transcription of Beethoven's "Eroica" Symphony, focusing on the complex technical and interpretative challenges involved in adapting an orchestral work for solo piano. Beethoven's "Eroica" Symphony is widely celebrated for its innovative structure and thematic development, and Liszt's transcription represents an effort to make such orchestral masterpieces accessible to solo pianists while retaining their expressive depth and grandeur. The research employs a comparative musical analysis methodology to explore the balance Liszt achieved between faithfulness to the original orchestration and pianistic feasibility. The study examines technical transcription techniques, such as the adaptation of orchestral textures into pianistic idioms, including imitating orchestral effect, descending octaves, and the mixing of voices to evoke the orchestral richness. Findings indicate that Liszt’s transcription is a transformative recreation rather than a simple reduction, showcasing his creative approach to translating orchestral music for piano. By preserving the formal structure while adapting textural and dynamic elements to suit the piano's capabilities, Liszt’s work exemplifies the delicate balance between fidelity to the original and artistic reinterpretation. This study contributes to the broader field of transcription studies by addressing gaps in the existing literature, particularly regarding the technical and interpretative strategies involved in transcribing orchestral music for a solo instrument.